Relation between Stuttering and Higher Brain Function - Yamamoto, Seiji; Sugiura, Syouji; Uemura, Kenichi; Igarashi, Ahemi; Kojima, Yoshiji (Higher Brain Function Research, 1989)
Pathogenesis of developmental stuttering is controversial. We have presented two interesting cases of stuttering and discussed the factors of stuttering. Case 1. A 53-year-old right handed male had developmental stuttering. In October, 1985, he developed left putaminal hemorrhage with right hemiparesis and Wernicke's aphasia. He did not stutter, while he had poor auditory comprehension and neglected his illness. But when his auditory comprehension was improved, his stuttering reappeared. Case 2. A 46-year-old right handed male had developmental stuttering. In February, 1984, he had left putaminal hemorrhage with Broca's aphasia and right hemiparesis. His auditory comprehension and awareness of his illness were not disturbed, and his stuttering did not disappear. The cerebral dominant theory (Orton and Travis' theory) alone cannot explain these cases of stuttering. If their cerebral dominancy had not been established, left putaminal hemorrhage might not have caused typical aphasia. We emphasize that the auditory comprehension and awareness of his illness -- monitoring system of speech -- is one of the most important factors of stuttering.